Prevalence of Tinea Versicolor among Dormitory Students - Soheil Taherpouran; Ali Asadi Zeidabadi Asadi Zeidabadi; Arian Alhani; Ensieh Lotfali (Novelty in Biomedicine)
Background: Tinea versicolor is a common cutaneous fungal infection of the skin caused by a part of the resident ﬂora of skin known as Malassezia species. This infection is recognized by pigmentation disturbance in the form of lesions and superficial scaling in the skin.